Conglomerates of Latin American countries and public policies for the sustainable development of the electric power generation sector (2018)
The investigation responded to the need outlined by directive and interested parts, in relation to the lack of mechanisms for the administration control and the need to reduce the amount of data when making measurements of performance in the cement industry. Throughout the employment of an outlined methodology, it was obtained an Integral Index of Acting that relates to the aspects that controlled the acting of the processes in function of managerial strategies, of easy mensuration as a result, automatic and that it facilitates to summarize a big amount of criteria and data, through their standardization, and thus the realization of comparisons with other production plants.